Opinion of Croatian Teacher Education Students Regarding the Quality of the Visual Arts Teaching Didactics Course - Županić Benić, Marijana (Revija za elementarno izobraževanje, 2017)
The purpose of this study was to assess student satisfaction with the Visual Arts Teaching Methodology course taught at the Croatian faculties of teacher education and identify important areas for improvement. The students’ open-ended, qualitative responses were reviewed and each response was assigned to one or more of the following categories: teacher performance, student teaching practice, assessment and grading, course organization, availability of learning materials and resources, and student teaching competences. The results indicate that the students are most satisfied with teacher performance, but they are also the least satisfied with course organization and recommend the most improvements in this area.
Keywords: course quality; student satisfaction; student opinions; didactics; visual art didactics